Deposisi ZnO Doping Ag pada Substrat Alumunium Foil untuk Degradasi Methylene Blue - Sheilla Rully Anggita (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2020)
This research has successfully deposited ZnO: Ag on aluminum foil substrates with variations in deposition temperature. The purpose of this study was to obtain the surface morphology of ZnO:Ag on aluminum foil substrates with variations in deposition temperature and obtain optimization of the photocatalytic activity of ZnO: Ag in degrading Methylene Blue dyes. ZnO:Ag deposition on the aluminum foil substrate was carried out by the sol-gel method and spray coating deposition technique. Surface morphology characterization and photocatalytic activity with SEM and with UV-Vis. The surface morphology results obtained from ZnO:Ag on aluminum foil substrate with deposition temperatures of 250 ?, 300 ?, 350 ?, and 400 ? are the forms of ganglia with indications as ZnO and Ag grains attached to ZnO. Obtained surface area and roughness level ZnO:Ag decreases with an increase in temperature from 250 ? - 300 ?, and surface area and roughness increases at 350 ? -400 ?. The highest level of roughness is found in the ZnO layer: Ag temperature 400 ?. The most optimum photocatalytic activity is indicated by the largest percentage of degradation. The highest percentage of degradation is shown by the ZnO: Ag layer with a temperature of 350 ? of 87.33%. This is due to the modification of silver at low temperatures which is <400 ? effective for photocatalytic activity.